Hubungan Antara Asupan Nutrisi dengan Kelancaran Produksi Asi pada Ibu yang Menyusui Bayi Usia 0-6 Bulan - Eny Pemilu Kusparlina (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2020)
ABSTRACT Each nursing mothers hope to breastfeed as much and as long as possible, as many (60%) nursing mother complained her milk production is not smooth so that they add milk with infant formula. In this case the nutrients and nutrition plays an important role in terms of supporting the maximum milk production lactating mothers food guided by a balanced diet 4 healthy 5 perfect, and the number of calories as much as 2400 to 2700 calories a day. The purpose of this study was to determine the relationship between the intake of nutrients with lactation in breastfeeding mothers of infants aged 0-6 months in the village Manisrejo, Taman district Madiun City. This type of research Analytical observational using cross sectional design. population as much as 30 mothers of infants aged 0-6 months, the sampling method is simple random sampling 28 lactating mothers of infants aged 0-6 months. Independent variable is the intake of nutrients, while the dependent variable is the smoothness of milk production. Collecting data using questionnaires with a nominal scale. Data were analyzed using Fisher exact formula. The results showed that the intake of nutrients, there are 22 mothers breastfeeding mothers (78.5%) with enough categories and 6 mothers (21.5%) with less category. While lactation there are 23 (82%) of mothers with milk production smoothly and there are five mothers (18%) with less milk production category or not current. Based on the test results p = 0.0034 ≤ α 0,05 so Ho rejected. Conclusion there is a relationship between the intake of nutrient with lactation. Suggestion to provide education on nutrition to breastfeeding mothers. Keywords: Nutrition intake, milk production Smoothness